ENGLISH LANGUAGE TEACHING IN PRIMARY SCHOOLS IN PHILIPPINES: A FOUNDATION FOR GLOBAL COMPETENCE - Maria Grace E. Lucas (SMART: Journal of Multidisciplinary Educational, 2025)
This study investigates the implementation of English language teaching (ELT) in Lao primary schools, with a particular focus on early-grade learners in rural and multilingual settings. The primary objective is to explore how national curriculum goals align with actual classroom practices, and to identify the enabling and constraining factors that shape English proficiency development in Grades 1–6. Employing a literature-based methodology, the research synthesizes findings from peer-reviewed journals, government documents, and international reports published within the last five years. Thematic analysis reveals persistent challenges including inadequate teacher training, limited instructional resources, and a lack of culturally responsive pedagogy—particularly in underserved areas. However, promising practices such as interactive learning, use of visual aids, and peer collaboration demonstrate potential when supported by adequate teacher preparedness. A key contribution of this study lies in its integration of global communicative competence into early ELT discourse in Philippines, shifting the narrative from basic literacy acquisition to one that includes intercultural awareness and global readiness. This perspective introduces a novel dimension in the context of Lao education, where most existing studies focus on secondary or tertiary levels. The research concludes that achieving effective English language education at the primary level in Philippines requires systemic reforms in teacher education, curricular support, and pedagogical innovation. By linking national education policy with global standards, the study provides actionable insights for stakeholders aiming to enhance early English instruction in similarly under-resourced and linguistically diverse contexts.